BETWEEN BEHAVIOURISM AND CONSTRUCTIVISM. - Raina, Vinod (Cultural Studies, 2011)
With over 400 spoken languages, a tribal (indigenous people) population of nearly 100 million, Hindu, Sikh, Christian, Jain and Muslim religions practiced by large sections of populations along with a myriad of other ethnic and cultural identities, flourishing local knowledge systems, social differences based on caste and class so palatable; defining a National system of education of good quality has remained a formidable and elusive challenge in India. Should the content reflect the cultural and social location of the child? Do local knowledge systems related to agriculture, health and medicine, artisanship and folk cultural forms have any place in the formal education system? If so, how should they be balanced with the more 'universal' forms of knowledge? What about language? Should it be mother tongue, Hindi and/or English - how many should be taught to a 10-year old child? Most of these questions apply to other post-colonial multicultural locations as well, around the World. Translated to pedagogy, the intense debate is whether the colonial pedagogies, deeply entrenched in indoctrinal forms of behaviourism ought to persist, or need they be replaced? While it is contented by many that a constructivist approach can accommodate the specific cultural roots of the child and aid in assimilating the child's knowledge into a larger knowledge system, critics have also warned of the risk of cultural relativism. For 30 years, between 1972 to 2002, many of these questions and challenges formed the basis of a very large experiment in improving the quality of school education in India, the Hoshangabad Science Education Programme (HSTP), which formed the basis of the latest National Curriculum Framework (NCF) formulated in 2005. The paper will use the empirical work of the HSTP and NCF2005 to address some of the questions raised earlier to indicate possible directions processes of quality education ought to take in multicultural contexts.